Was John Wesley a Racist? Excavating the Foundations of British Methodism’s Epistemological Whiteness - Morris-Chapman, Daniel Pratt (Black theology, 2026)
In spite of its emphasis on equality, diversity and inclusion, British Methodism has been heavily critiqued for its epistemological Whiteness. This essay probes the epistemological roots of this problem by exploring the views of the founder of the Methodist movement. There are a number of studies concerning John Wesley’s responses to slavery and indeed a good number of studies concerning Methodist efforts to end this trade in human trafficking. However, aside from Natalia Cherry’s analysis of the racism of certain abolitionists in the United States during the Antebellum period, little attention has been given to the question as to whether Wesley himself was both anti-slavery and racist. Through an examination of John Wesley’s interactions within his journals, sermons and various other writings, this paper will examine his views in order to explore whether or not he may form a part of the problem facing contemporary Methodism.